2019
DOI: 10.1101/775940
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Coconut inflorescence sap mediated synthesis of silver nanoparticles and its diverse antimicrobial properties

Abstract: Green synthesis of nanoparticles (NPs) involves the use of diverse extracts of biological origin as substrates to synthesize nanoparticles and can overcome the hazards associated with chemical 2 methods. Coconut inflorescence sap, which is unfermented phloem sap obtained by tapping of coconut inflorescence, is a rich source of sugars and secondary metabolites. In this study, coconut inflorescence sap was used to synthesize silver nanoparticles (AgNPs). We have initially undertaken metabolomic profiling of coco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 56 publications
(56 reference statements)
1
5
0
Order By: Relevance
“…The data presented is an average calculation of 200 particles (Image J software) plotted by Origen Pro. Silver nanoparticles synthesized from coconut inflorescence sap and leaf extracts measured between 10 and 30 nm, which is in perfect agreement with the present study 72 , 75 . The average size measured by the zeta sizer showed low PDI but larger particles in comparison to TEM measurements due to the fact that DLS measurements are taken in a liquid state (solution) and include the size of the metallic core, phytochemicals (coatings), and the layer of solution, unlike TEM measurements, which measure solely the metallic core 76 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The data presented is an average calculation of 200 particles (Image J software) plotted by Origen Pro. Silver nanoparticles synthesized from coconut inflorescence sap and leaf extracts measured between 10 and 30 nm, which is in perfect agreement with the present study 72 , 75 . The average size measured by the zeta sizer showed low PDI but larger particles in comparison to TEM measurements due to the fact that DLS measurements are taken in a liquid state (solution) and include the size of the metallic core, phytochemicals (coatings), and the layer of solution, unlike TEM measurements, which measure solely the metallic core 76 .…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have reported similar variations in peak positions 10 , 71 . The FTIR spectra of AgNPs synthesized using coconut inflorescence sap surprisingly showed peaks in similar positions (2990 cm −1 , 2912 cm −1 , 1100 cm −1 ); these peaks were attributed to CH 2 stretching vibration of the pyrrole ring and C–C–CH 2 linkage of a long carbon 71 , 72 . Earlier studies have reported coconut meat and coconut water as rich sources of dietary fibers, proteins, amino acids, and alkaloids, which authenticates the present findings 73 , 74 .…”
Section: Discussionmentioning
confidence: 94%
“…The main bioactive compounds present in olive fruit (OF) are phytochemicals including flavonoids, phenolic acids, terpenoids, phenolic alcohols, sugars, proteins, alkaloids, secoiridoids, and hydroxycinnamic acid derivatives ( Ghanbari et al, 2012 ), which can act as reducing agents, stabilizers, and capping agents during nanoparticle synthesis. Natural antioxidants extracted from plants, especially phenolics and flavonoids ( e.g ., ferulic acid, gallic acid, kaempferol, quercetin, and catechins), have been examined as antioxidant-based antibacterial agents and demonstrated promising effects to overcome the resistance of various microbes versus synthetic antibiotics ( Rajesh et al, 2020 ). Additionally, when combined with silver nanoparticles, plant extracts can exhibit synergistic effects, enhancing their antibacterial activity and colloidal stability compared to other traditional capping agents and biomolecules ( Some et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…A study shows the good biocompatibility stability of Gd-based CIS/ZnS nanoprobes for in vitro cytotoxicity . The literature states that the incorporation of plant extracts such as Azadirachta indica (neem), , Ocimum sanctum (basil), , Cocos nucifera (coconut), Aloe vera (aloe), , Curcuma longa (turmeric), and so forth during synthesis makes the NPs biocompatible. The incorporation of green extracts improves the antimicrobial, antioxidant, and cytotoxicity activities of the NPs. Apprehending the significance of CIS NPs, the authors decided to study them for biological applications.…”
Section: Introductionmentioning
confidence: 99%